Social prescribing for Not in Employment, Education or Training (NEET) young people: A realist evaluation of the C.O.P.E. project in Italy and Portugal - Marcello Bertotti; Isabel Farina; Maria J. Marques; Regina Alves; Sonia Dias; Sara Paternoster; Anita Paza; Emanuele Torri (SSM - Mental Health)
NEET (Not in Employment, Education, or Training) status is associated with psychological distress and suicidality. Social prescribing may offer a policy solution to this. To test this proposition, this study evaluates the mental health outcomes of a social prescribing intervention—C.O.P.E. (Capabilities, Opportunities, Places, and Engagement) project—on young people in a NEET situation in Italy and Portugal. Adopting a realist evaluation approach, this study explores how context and mechanisms interact to generate outcomes. A realist synthesis of NEET interventions and co-production with stakeholders helped to create a programme theory which was tested through a mixed-methods study, combining quantitative cohort data from 416 young people with qualitative interviews with 30 young people, 13 link workers, and 9 team members. The findings indicate significant improvements in mental wellbeing and reductions in psychological distress, particularly among those with clinical mental health issues. Qualitative insights emphasise the importance of trust between link workers and young people, highlighting flexibility, emotional support, and a holistic approach as key factors in fostering engagement. This led to the creation of three programme theories. One of these focuses on young people and is discussed in this article. The study concludes that despite some challenges related to sustainability, training and long-term impact, social prescribing can be an effective tool for supporting youth in a NEET situation, particularly those suffering clinical mental health issues. This paper contributes to the growing evidence supporting social prescribing as an approach to enhance mental health and social inclusion for youth in vulnerable situations.